Techno-economic analysis of a PV system with a battery energy storage system for small households: A case study in Rwanda - Nkuriyingoma, Obed; Özdemir, Engin; Sezen, Serkan (Frontiers in Energy Research, 2022)
Due to the inadequacy of distribution networks in developing countries, especially in small residential areas, there are frequent interruptions in the electrical energy provided by the grid. This problem negatively affects the life quality and productivity of the people living in these regions. This problem can be overcome by integrating BESS-supported renewable energy sources into the distribution system. These distributed energy resources contribute significantly to providing energy directly to consumers. On a small scale, such a system is supported by the grid, when possible, to ensure energy supply continuity. This study presents a techno-economic analysis, using PV*SOL simulation software, of a grid-connected solar PV system with BESS that is used to supply a small residential community in Rwanda, Muhanga district, Shyogwe sector. The consumers were a group of one hundred households around a wetland valley. The energy generated from the solar PV system was used to supply home appliances and a water pumping system for agricultural activities. The simulation results showed that the annual energy requirement is 82.34 MWh with a peak load of 30.4 kW. The simulation results also revealed that a PV system, with an installed capacity of 57.33 kWp integrated with a BESS of 89.2 kWh storage capacity, can supply the load with own power consumption of 68.65%, a level of self-sufficiency of 64.38%, and a performance ratio of 86.05% when the desired ratio is set to 110% with a year as the reference period. The financial analysis demonstrated a return on assets of 9.14% and an amortization period of 9.65 years. These results indicate that the proposed method is technically and economically feasible for use in addressing the issue of electrical power outages in developing countries.